Explicit professionalism. A cross-level study of institutional change in the wake of evidence-based practice. Issue 2 (15th May 2019) - Møller, Anne M
Abstract: This article shows how a new normative standard for public professionalism has evolved from the introduction of evidence-based practice in Danish child protective services. The concept of 'theorization' from institutional theory is discussed and applied as the main analytical lens to explore how new ideas are introduced, interpreted, and negotiated in the organizational field. Based on a cross-level ethnographic case study, the study traces the process of theorization and shows how actors are informed by local translations and theorizations as they challenge, negotiate and develop collective understandings in the field. Theorization is therefore conceptualized as a continuous multidirectional process of recursive intertwinement between field-level and organizational developments, which may or may not entail institutional change. The study also contributes to our understanding of changing forms of professionalism by proposing the concept 'explicit professionalism' as a way of capturing the new normative standard for public professional work that has evolved from the process of theorizing evidence-based practice. Explicit professionalism is both a descriptive concept and a normative ideal and, it is suggested, an important dimension of new forms of organizational and organizing professionalism, which can aid our understanding of related developments in different professional fields.